Effects of Understory Vegetation Management on Plant Communities in Oil Palm Plantations in Sumatra, Indonesia - Luke, Sarah H.; Purnomo, Dedi; Advento, Andreas Dwi; Aryawan, Anak Agung Ketut; Naim, Mohammad; Pikstein, Rachel N.; Ps, Sudharto; Rambe, T. Dzulfikar S.; Soeprapto,; Caliman, Jean-Pierre; Snaddon, Jake L.; Foster, William A.; et al. (Frontiers in Forests and Global Change, 2019)
Oil palm plantations have expanded rapidly in recent decades, and are causing substantial impacts on tropical habitats and biodiversity. However, owing to its long lifespan (25-30 years), oil palm forms a much more varied and structurally-complex habitat than many other crops. This can include abundant understory vegetation and also epiphytes on palm trunks. However, the diversity of this plantation vegetation has been poorly studied, and there has been little consideration of the impacts of common plantation vegetation management practices on plant communities. We conducted a long-term vegetation management experiment that forms part of the Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Programme in Riau, Indonesia. We manipulated herbicide and manual cutting regimes within mature oil palm plantations to create three different understory complexity treatments (Reduced, Normal, and Enhanced vegetation) across replicated sets of plots. Plant communities were surveyed before and after experimental understory vegetation treatments began in three different microhabitats: within the middle of the plantation block (core), on the road edge (edge) and on oil palm trunks (trunk). Part of the sampling was also conducted during a drought event. We recorded 120 plant species, which comprised a mixture of native, non-native, ‘beneficial’, and ‘problem’ species. We found substantial variation in plant communities between edge, core, and trunk microhabitats, indicating high levels of heterogeneity within the plantation. There were significant effects of varying understory treatment within both core and edge microhabitats, but no spillover of impacts into the trunk microhabitat. We also observed substantial impacts of drought on plant communities, with declines in either biomass, percentage cover, or richness seen across core, edge, and trunk microhabitats during low-rainfall periods. Our findings highlight the diversity of plant communities that can be supported within oil palm plantations, and the substantial impacts that management decisions, and also drought, can have on them. Given the role that diverse plant communities can have in supporting species in other groups, this is likely to have a significant impact on the wider plantation biodiversity. We suggest that plantation management strategies give greater consideration to within-plantation understory plant communities and choose more wildlife-friendly options where possible.